Economic Analysis Of The Response Of Broad Beans to Levels Of Phosphate Frtilizers Westren South Of Tripoli- Libya - Khaled R. Elbeydi, Mabrouk Elsharief , Husseen Elsouae (Journal of Pure & Applied Sciences, 2018)
This study aimed to estimate the optimum amount of phosphate fertilizers for broad beans production in experiment carried out at ZAHRA research station western south of Tripoli region, An experiment were conducted during four seasons ( 2001 - 2005 ) to study the effect of phosphorus fertilizer application on Fababean yield(green and dry ) . The experiment, were repeated four years ,with Design ( RCBD) in four replicates and Five rates of phosphorus fertilizers ( 0 ,30 ,60, 90 and , 120 ,) kg P2O5 /ha were used , the local variety " Aquadolce" was used. Quadtric production function was used by applying regression analysis The results showed that there were significant differences in all Agronomic characteristics measured. The results had shown that the optimum amount of phosphorus fertilizer was (191) kilo gram/hectare.